Pemasaran, Daya Tarik Ekowisata, dan Minat Berkunjung Wisatawan - Kurniawan Gilang Widagdyo (Esensi: Jurnal Bisnis dan Manajemen, 2017)
Marketing, Eco-tourism Interest and Visitors' Interest This research aims to analyze the potential of ecological tourism interest in Cipta Gelar Traditional Village West Java Indonesia and determine interest factors that have implication on visit intention domestic visitors. This research used survey, observation and indepth interview of stakeholders. Factor analysis used to analize interest factors toward ecological tourism that have implication on visit intention of domestic visitors. Three factors was formed there are Adventure and Culture factors, Tourism Interest and Natural Beauty, and History and Social Values. From those three factors, it is only factor 1 and 3 that imfluence on visit intention with correlation value among factors more than  0,5 there are 0,641 and 0,705. Meanwhile, factor 2 has value less than 0,5 that is 0,402. It has correlation with another factors that is not included in this research.DOI: 10.15408/ess.v7i2.5411